(untitled) (Al-Qamar, 2023)
This article briefly reviews traditional and modern tafsir (interpretation) trends and how modern Tafasīr have shaped contemporary Islamic thoughts. Classical Tafsir trends, Tafsir Bi al- ma’thur (tradition-based interpretation) and Tafsir Bi al-ra’y (reason-based interpretation) are well-documented in historical norms of Qur’ānic exegesis. However, modernity, with its complex socioeconomic, religious, political and cultural developments, presents unique challenges to interpreters (authors of Qur’ānic interpretations) to contextualize the Qur’ānic message and provide guidance to modern- day Muslims and their worldview. Complex modern Islamic thought is a selection of ideologies and philosophies that resulted from the prevailing diverse geopolitical, sociocultural and economic environment. These dynamic elements of modernity have conceptualized tafsir trends into the textualist, contextualize, modernist, socio-political, scientific, thematic and feminist approaches. These trends have not only transformed contemporary Islamic thought, and vice versa, but also continue to collectively evolve to meet the challenges of modernity. This article briefly reviews traditional and modern tafsir (interpretation) trends and how modern tafasir have shaped contemporary Islamic thought. Classical tafsir trends, tafsir bi al- ma’thur (tradition-based interpretation) and tafsir bi al-ra’y (reason-based interpretation) are well-documented in historical norms of Qur’ānic exegesis.